2008
DOI: 10.1007/s00213-008-1266-9
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of the development and expression of ethanol-induced behavioral sensitization in female Swiss mice: effects of dose, injection schedule, and test context

Abstract: Female Swiss mice develop a robust context-independent sensitization after repeated ethanol injections at all doses above 1.5 g/kg, including highly sedative doses such as 4 g/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 38 publications
7
49
4
Order By: Relevance
“…Thus it would appear that antagonism of the NMDAR abolishes contextual conditioning. In mice, the development of behavioural sensitisation to ethanol, an indirect NMDAR antagonist, was also reported to be independent of environmental context (Didone et al, 2008) as has been observed with the direct NMDAR antagonists MK-801 (present study) and PCP (Clark et al, 2002, Xu andDomino, 1994b). Overall, the absence of environmental contextual modulation on MK-801 sensitisation reported in this study is congruent with the literature.…”
Section: Experiments 22: Effect Of Environmental Context On Mk-801-insupporting
confidence: 92%
See 2 more Smart Citations
“…Thus it would appear that antagonism of the NMDAR abolishes contextual conditioning. In mice, the development of behavioural sensitisation to ethanol, an indirect NMDAR antagonist, was also reported to be independent of environmental context (Didone et al, 2008) as has been observed with the direct NMDAR antagonists MK-801 (present study) and PCP (Clark et al, 2002, Xu andDomino, 1994b). Overall, the absence of environmental contextual modulation on MK-801 sensitisation reported in this study is congruent with the literature.…”
Section: Experiments 22: Effect Of Environmental Context On Mk-801-insupporting
confidence: 92%
“…It is postulated that the enhancing effect of environmental context on drug-induced behavioural sensitisation is due in part to a learning and memory process dependent on activation of NMDARs (Battisti et al, 2000, Battisti et al, 1999. Therefore it is not surprising that drugs that antagonize NMDARs such as PCP and ethanol (Lovinger et al, 1989b), are also not modulated by environmental context , Xu and Domino, 1994, Didone et al, 2008. Our study is the first to provide evidence that sensitisation to MK-801 is not modulated by environmental context.…”
Section: Mk-801 Sensitisation and Stress Signallingmentioning
confidence: 58%
See 1 more Smart Citation
“…injection of saline solution and were immediately placed into the center of the locomotor monitoring chamber. Locomotor activity was recorded for the next 5 min in the LE 8811 IR motor activity monitor (Bioseb, Vitrolles, France) to specifically capture the stimulant effects occurring during the ascending limb of the blood alcohol concentrations [42]. Mice were then divided into Saline-(n = 30) and EtOH-(n = 40) treated groups that were equated in terms of horizontal locomotion on day H. During 10 days (day 1 -day 10), mice received one daily i.p.…”
Section: Eibs Proceduresmentioning
confidence: 99%
“…Locomotor activity, as a measure of spontaneous behavior, has been primarily assessed in behavioral sensitization studies (14,15). Additionally, behavioral sensitization has been established in rodents that have repeatedly been administered the same or incremental doses of a drug (16)(17)(18)(19). It has been demonstrated that behavioral sensitization may also be applied in a model of testing addictive behavior associated with drug seeking and relapse (12,20).…”
Section: Introductionmentioning
confidence: 99%